Diaphragm Disease: The Limitation of Laparoscopy and Assessment of the Small Bowel for Strictures Using a Ball Bearing - C.E. Moffat; M.N. Khyan; C.G. Davies; A.S.K. Ghauri; C.J. Ranaboldo (The Scientific World Journal)
Diaphragm disease is a rare cause of intestinal obstruction that will be seen with increasing frequency with the widespread use of nonsteroidal anti-inflammatory drugs (NSAIDs). We present a case study of a patient with diaphragm disease where the diagnosis was not apparent at laparoscopy, and passage of a steel ball through the small intestine was required to identify all strictures present. A high index of suspicion, recognition of the limitations of conventional diagnostic aids, and the need to assess the full length of the small bowel are all important in the surgical management of this condition.